Serum zinc level and prognosis of neonatal sepsis - Chaliza Adnan; I Wayan Dharma Artana; Ketut Suarta; I Gusti Lanang Sidiartha; I Wayan Gustawan; Ni Putu Veny Kartika Yantie (Indonesian Pediatric Society, 2020)
Background The prognosis of neonatal sepsis can be influenced by various risk factors, one of which is a deficiency of zinc micronutrient substances. Objective To assess for a potential association between serum zinc level and prognosis of infants with early-onset neonatal sepsis (EONS). Methods This prospective cohort study was done in neonates with clinical EONS from September 2017 until December 2018. Serum zinc level was measured on the first day of diagnosis and prognosis was assessed on the fourth day. The association between serum zinc levels and prognosis of EONS was analyzed by Chi-square test and logistic regression with adjustment for confounding variables. Results A total of 70 subjects were divided into two groups based on their serum zinc levels. A cut-off point of 75 ug/dL was used based on area under the curve (sensitivity 91.2% and specificity 93.7%), with accuracy 97.8% (95%CI 0.943 to 1.000; P=0.0001). Subjects with lowzinc level had a 16.8 times greater risk compared to subjects with high serum zinc (RR=16.81; 95% CI 4.35 to 65.02; P <0.0001). Multivariate analysis revealed that subjects with low serum zinc levels had 203.7 times greater risk of worsening than subjects who had a higher serum zinc level (RR 203.72; 95% CI 26.79 to 1549.17; P <0.0001). Covariates such as male sex, low gestational age (<37 weeks), low birth weight (<2,500 grams), asphyxia, Caesarean section delivery, and the presence of comorbidities did not have significant associations with outcomes of EONS (P >0.05). Conclusion Serum zinc level is associated with prognosis of early onset neonatal sepsis, with a cut-off of 75 Î¼g/dL. The high level of serum zinc associates with a better prognosis.